ANALISIS TINGKAT PEMAHAMAN MASYARAKAT MUSLIM DI PERUMAHAN GRAND PARAMOUNT LEBIH MEMILIH MENGGUNAKAN AKAD KPR KONVENSIONAL - Muhamad Subhan; Neneng Sudharyati; Muhamad Filza Thriyandha (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The researcher's observation on initial observations found that the problem why Muslim communities in grand housing prefer to use conventional mortgages is be- cause of the lack of public understanding of the concept of sharia mortgages them- selves. According to researchers, the cause of the lack of public interest in applying for sharia mortgages is that the understanding provided by the developer about the difference between sharia mortgages and conventional mortgages is still not com- prehensive. However, not a few people think that the concepts in sharia mortgages and conventional mortgages are the same, and this is what underlies people still using conventional mortgages. The research method used in this study is qualitative method, with a case study approach design. The results showed, 1. The level of public understanding of the concept of KPR Shari'ah: a. the community does not understand the concept of KPR syariah., b. the community does not understand the concept of KPR syariah., c. the public under- stands the concept of sharia mortgage. 2. Reasons why people prefer to use conven- tional mortgage contracts over shari'ah mortgages: a. difficulties when selecting files., b. high DP offered., c. convenience offered by conventional mortgages., d. no offers from the devloper.